A case of recurrent pneumothoraces in a newborn. Issue 4 (4th February 2022) - George, Ashish; Ortenberg, Robin; Pinto, Swaroop
Abstract: Pneumothoraces are not an uncommon finding in the newborn period. Recurrent pneumothoraces can be associated with complications of prematurity or use of ventilators but can be seen in rapidly progressive cystic lung disease. We report a case of recurrent pneumothoraces in an infant with the rapidly progressive cystic disease in the setting of an absent right pulmonary artery. The patient ultimately underwent pneumonectomy for definitive management of the recurrent unilateral pneumothoraces.